Comunidade fitoplanctônica da sub-bacia do rio Baía, planície de inundação do alto rio Paraná : variabilidade interanual e persistência das espécies. - Bortolini, Jascieli Carla (2014)
A study was conducted concerning the interannual variability and persistence of phytoplankton species in a sub-basin of the upper Paraná River floodplain, which included a large temporal scale and several environments, during potamophasis and limnophasis periods. In the first, a long-term study was conducted, covering 12 hydrosedimentological cycles, on variability of phytoplankton biovolume and functional groups, involving the Baía River, a connected lake and a isloated lake. Was measured the influence of extreme hydrological periods, being one with a long limnophasis period and another one with a conspicuous potamophase, we analyzed the effects of these periods on the phytoplankton variability and persistence in the Baía River basin. Was evaluated the distribution and spatiotemporal dominance of cyanobacteria populations during two hydrosedimentological cycles, in the Baía river, in four connected lakes, four isolated lakes and two active channels. Established that the stability and temporal variability of biovolume and functional groups were linked to seasonal and interannual variability of limnophasis and potamophasis periods, which in turn, were related to long-term effects of climate variability and anthropogenic events. The results showed that the extension of limnophasis decresead the phytoplankton richness and influenced the pattern of dominance and persistence of species. There was also an increase of cyanobacteria in the sub-basin of the Baía River due to the lower connectivity of habitat and the highest concentrations of nutrients during limnophasis.